2009
DOI: 10.1021/jp809835a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic (γ-Fe2O3@SiO2)n@TiO2 Functional Hybrid Nanoparticles with Actived Photocatalytic Ability

Abstract: An easy chemical route for the synthesis of (γ-Fe 2 O 3 @SiO 2 ) n @TiO 2 functional hybrid nanoparticles is reported in this paper. The hybrid nanoparticles are composed of spherical nanoparticles about 100 nm in diameter, with several γ-Fe 2 O 3 fine particles about 15 nm in diameter as cores distributing within the titania matrix and silica as coatings and barrier layers between the magnetic cores and titania shells. The (γ-Fe 2 O 3 @SiO 2 ) n @TiO 2 hybrid nanoparticles show good magnetic response and got … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 23 publications
0
60
0
7
Order By: Relevance
“…It has been found that the addition of a silica layer between an iron oxide core and a titania shell promotes the photocatalytic activity of the catalyst by decreasing the adverse influence of the magnetic oxide core. [22,23] However, in prior studies the photocatalytic activity of the hybrid spheres did not show much improvement when compared with single-phase anatase particles, probably due to the limited control over the crystallinity and size of the supported TiO 2 nanocatalysts.…”
Section: Introductionmentioning
confidence: 93%
“…It has been found that the addition of a silica layer between an iron oxide core and a titania shell promotes the photocatalytic activity of the catalyst by decreasing the adverse influence of the magnetic oxide core. [22,23] However, in prior studies the photocatalytic activity of the hybrid spheres did not show much improvement when compared with single-phase anatase particles, probably due to the limited control over the crystallinity and size of the supported TiO 2 nanocatalysts.…”
Section: Introductionmentioning
confidence: 93%
“…1A-a and A- (Fig. 1B) [32][33][34][35]. During calcination process, bare Fe 3 O 4 not only contacts with oxygen more thoroughly but also experiences more thermal radiation when compared with Fe 3 O 4 enclosed by SiO 2 and AgBr, favorable to the formation of more thermodynamically stable ˛-Fe 2 O 3 rather than metastableFe 2 O 3 .…”
Section: Morphology and Microstructuresmentioning
confidence: 99%
“…The unique properties of magnetic NPs and nanocomposite particles (NCPs), such as their high surface area and catalyst loading, convenient catalyst recycling, considerable dispersion, and outstanding stability, have led to increased attention to these materials (Chi et al 2012). In order to magnetically separate and recycle TiO 2 nanocatalysts, a variety of TiO 2 /iron oxide nanocomposites have been prepared and evaluated (Xuan et al 2008;Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although the direct coating of TiO 2 on the surface of magnetic particles could protect the sensitive and unstable magnetic NPs, specially under acidic conditions against chemical corrosion, but the direct coating may lead to a photodissolution phenomenon which not only changes the properties of the magnetic oxides but also decreases the photocatalytic activity of TiO 2 . Due to its chemical inertia, silica (SiO 2 ) has been proposed to be added between the magnetic particles core and TiO 2 coating to overcome the above-mentioned problems (Wang et al 2009). The application of an intermediate layer barrier such as SiO 2 between the magnetic core and the titanium dioxide shell may lead to the avoidance of the photodissolution of iron, magnetic core stabilization, and the prevention of the magnetic core from acting as an electron-hole recombination center which would negatively affect the photoactivity of TiO 2 NPs Abramson et al 2009).…”
Section: Introductionmentioning
confidence: 99%